D12 DNA damage signatures in peripheral lymphocytes as biomarkers in prodromal huntington disease. (September 2018) - Romano, C; Morena, E; Castaldo, I; Migliore, S; Borrelli, C; Peluso, S; Salvatore, E; Mondo, A Del; Michele, G De; Squitieri, F; Ristori, G; Avvedimento, EV; et al.
Abstract : Background: Blood biomarkers to improve the management of pre-manifest Huntington's disease (pre-HD) are actively searched We investigated the telomere length (TL) and DNA damage signatures (DDS) in peripheral lymphocytes from pre-HD individuals and HD patients, as potential predictive biomarkers. Methods: We studied 58 HD and 23 pre-HD subjects with comparable CAG repeats, and 44 age/sex-matched healthy controls (HC). Phosphorylated γ-H2AX (pγ-H2AX) fluorescence, which marks double strand DNA breaks, and the TL were studied by cytofluorimetry and qPCR. Results: Peripheral lymphocytes from pre-HD and HD groups showed significant DDS than HC. The odds ratio was <0.001 (HC vs HD: t-test p<0.0001, Logistic Fit ChiSquare 20.59, p<0.0001, ROC Area 0.87; HC vs pre-HD: t-test p<0.0001, Logistic Fit ChiSquare26.04, p<0.0001, ROC Area 0.96). All patients showed shorter telomeres compared to HC; the odds ratio was <0.001 (HC vs HD: t-test p<0.0001; Logistic Fit ChiSquare 20.77, p<0.0001; ROC Area 0.75). Four individuals with pre-HD were analyzed at several time points: pγ-H2AX signal increased overtime; in three of them pγ-H2AX decreased after the appearance of clinical signs, although remaining higher compared to HC. In the pre-HD group the levels of pγ-H2AX correlated with the progression rate of the HD phenotype, measured three years later and accurately predicted disease onset. Conclusions: Peripheral lymphocytes from pre-HD subjects display progressive DDS in absence of clinical and signs. The basal levels of DDS are predictive of disease progression over time. DDS may represent a biomarker with unprecedented features (accessible, clearly detectable in pre-manifest HD, negligible HC, potential reversible).